ANALISIS PELAKSANAAN PPL TERBIMBING MAHASISWA PPG CALON GURU TAHUN 2026 UNIVERSITAS ADZKIA DI SDIT ADZKIA 2 PADANG - Wina Apriana; Dika Febri Yenita; Hayfa Dzakiyyah; Muzila Tunil Isma; Nahda Navilah Daulay; Septiana Heptalita; Maifit Hendriani (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study was motivated by the importance of guided teaching practice in developing the professional competencies of PPG students as prospective educators. The study aims to describe the implementation of guided teaching practice for PPG students prospective teachers of the 2026 cohort from the LPTK at Adzkia University at SDIT Adzkia 2 in Padang. The study employed a descriptive qualitative approach using observation, interviews, and documentation techniques. The results indicate that the implementation of the PPL program, through stages of orientation, observation, teaching assistance, and guided teaching practice, effectively enhances students’ pedagogical skills, classroom management, instructional material development, and reflective skills. Although challenges such as time management and classroom management still exist, students were able to make improvements through continuous guidance and evaluation. In conclusion, Guided PPL is effective in supporting the professional competencies of prospective educators.